Standardized construction of a porcine model for acute obstructive jaundice and training of endoscopic ultrasound-guided choledochoduodenostomy - Zhou, Xue; Liu, Ziming; Ma, Wenzhuang; Sheng, Shiyun; Sun, Siyu; Ge, Nan (Frontiers in Oncology, 2023)
Background: Endoscopic ultrasound-guided biliary drainage (EUS-BD) is an alternative to endoscopic retrograde cholangiopancreatography (ERCP) for patients with obstructive jaundice. However, it is still a challenge for many endoscopists because of its novelty and complexity. This study aimed to establish an ideal bile duct dilatation model for the training and practice of endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS).: The 34 healthy Bama miniature pigs were divided into the part of developing the standardized EUS-CDS (n=9) and the part of trainees training (n=25). Part one, two different methods were used to clip Vater's ampulla using metal clips to establish an extrahepatic bile duct dilatation model. Part two, five trainees were trained on EUS-CDS with 25 pigs. Following a 2-week observation period, the feasibility and effectiveness of the technique were evaluated.Results: In the group with three metal clips perpendicular to the duodenal wall clipping Vater's ampulla, the success rate of extrahepatic bile duct dilation greater than 1 cm in 24 h was 5/6, whereas the remaining one pig was 48 h. All five trainees can finally complete the EUS-CDS independently. No death occurred during the 2-week observation period.Clipping Vater's ampulla with three metal clips perpendicular to the duodenal wall is an effective and stable method to create a porcine bile duct dilatation model.